Sœ̄msāng khwāmkhēmkhæng khrō̜pkhrūa læ chumchon nai kānčhatkān sukkhaphāp - Suphattrā Sīwanitchākō̜n (Sathāban Phatthanā Sukkhaphāp ʻĀsīan, Mahāwitthayālai Mahidon], 2011)
Compilation of articles on community participation in health management of Thai families and communities.